Lumbung Yusuf : Peran Gereja dalam Pelayanan Diakonia di Tengah Masa Pandemi Covid-19 - Roy Pieter; Sri Wahyuni; Josiharu EF Here (STT Kingdom, 2021)
Diakonia as a responsible gospel ministry with actions and words carried out by Christians in responding to people's needs, through the Covid-19 pandemic situation the Church is required to play its role and function through diaconian services for church members. This study aims to examine the role of the church in carrying out diaconian services for church members who are affected by the Covid-19 pandemic. The research method used is a qualitative approach with descriptive methods. The results of this study indicate that the role of the church in the service of the diaconate known as the Lumbung Yusuf program is very significant both in its existence and in its usefulness for church members who are affected by the Covid-19 pandemic